Prototype Energy Saving Car Chassis Design and Analysis Using 6061 Aluminum Material : Perancangan Desain dan Analisa Chassis Mobil Hemat Energi Tipe Prototype dengan Material Aluminium 6061 - Pangestu, Eka Adji; Fahruddin, A'rasy; Akbar, Ali; Firdaus, Rachmat; Iswanto; Nia Nuraeni Suryaman (Universitas Muhammadiyah Sidoarjo, 2024)
The chassis is an important component car which functions to support the load on the vehicle and has a strong construction. The chassis, as the main support for all vehicle componentsy. Increased fuel use and rising global crude oil prices have encouraged research into energy saving cars with special designs that can reduce fuel consumption and pollutant emissions. The design process with variations in rollbar shape and variations in cross sectional shape with 6061 aluminum material using Autodesk Inventor 2024 software. After the design process is complete, stress analysis test stage is carried out to obtain analysis data, namely von misses stress, strain, displacement, safety factor. The results of the chassis design using concept B with a pipe cross-sectional shape and rollbar fillet model are more recommended, because it has better von Mises stress value and a better safety factor, besides that the concept B chassis design is easier in the assembly process with prototype type energy efficient car body.